Analisis Tren Penggunaan Teknologi Loop-Mediated Isothermal Amplification (LAMP) sebagai Alternatif PCR: Kajian Literatur - Erika Dwi Susanti; Elsa Trisna Sari; Devina Adira Azzahra; David Valentino Iskandar; Nasywarana Putri Panjaitan; Khotimah Nur Ramadhani; Juwita Ramadhani Octavianingrum; Elsa Oktavia Ramadhani; Liss Dyah Dewi Arini (The Journal General Health and Pharmaceutical Sciences Research, 2026)
Gene amplification technology plays a crucial role in medical diagnostics. While Polymerase Chain Reaction (PCR) is widely regarded as the standard method for amplifying nucleic acids, its reliance on a thermocycler restricts its use in settings with limited resources. As an alternative, Loop-Mediated Isothermal Amplification (LAMP) has gained attention for its ability to perform specific and fast amplification at a constant temperature, eliminating the need for temperature cycling. The goal of this literature review is to examine the global developments and usage of LAMP technology, comparing it with PCR as a possible alternative. To achieve this, a systematic review of scientific articles from both international and national sources was conducted, focusing on the application, validation, and comparison of LAMP with PCR. The findings show a rising number of publications and patents related to LAMP, especially in areas like diagnosing infectious diseases and conducting point-of-care (POC) testing. This growth is attributed to the benefits of LAMP, such as its high sensitivity, quick results, and ease of detection through visual means without the need for electrophoresis. In summary, LAMP is showing great promise as a transformative diagnostic tool. The rapid growth in its adoption suggests that it is becoming a strong alternative to PCR for real-time and affordable diagnostic applications in various settings.